Designing Job Stress Management Strategies for Primary School Teachers - Chen, Kai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This study focuses on the factors that influence the work stress of primary school teachers and recommends strategies to relieve the work stress. In this study, 294 primary school teachers in the Tianfu New Area in Sichuan China were surveyed using an online questionnaire. The quantitative results of descriptive and inferential statistical analysis show that ambiguity of role, workload, lack of autonomy and relationship with others have significant influence on primary school teachers' work stress. Based on the results of this study strategies for organizations and individuals to deal with teachers' stress were recommended.